Analisis Aktivasi dan Deaktivasi Layanan Internet Bisnis Pendekatan Berdasarkan PSAK 115 IndiBiz - Muhamat Abdul Rozak Rifai; Fabio Bolanda Sandy (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
PT Telkom Indonesia Witel Yogya Jateng Selatan Area Magelang is an information and communication technology institution that provides connectivity and digital services to meet the needs of the community. This study aims to analyze the conformity of revenue recognition for IndiBiz service contracts with the provisions regulated in PSAK 115 concerning revenue from contracts with customers at PT Telkom Indonesia Witel Yogya Jateng Selatan Area Magelang. The conformity of revenue recognition with PSAK 115 is important to ensure transparency and reliability for both customers and service providers. This research uses a qualitative method with a case study approach. Data were collected through in-depth interviews with relevant parties, direct observation, and document analysis related to the implementation of service contracts and revenue recognition procedures. The results of this study indicate that revenue recognition for IndiBiz service contracts is carried out on a monthly basis using the continuous service delivery method over time. This practice reflects the fulfillment of the company’s performance obligations during the service period. Therefore, the revenue recognition applied by the company has been implemented in accordance with the provisions of PSAK 115 regarding revenue from contracts with customers.